2013
DOI: 10.1523/jneurosci.0784-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Modeling by the Cerebellum Improves Proprioception

Abstract: Because sensation is delayed, real-time movement control requires not just sensing, but also predicting limb position, a function hypothesized for the cerebellum. Such cerebellar predictions could contribute to perception of limb position (i.e., proprioception), particularly when a person actively moves the limb. Here we show that human cerebellar patients have proprioceptive deficits compared with controls during active movement, but not when the arm is moved passively. Furthermore, when healthy subjects move… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
120
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(139 citation statements)
references
References 28 publications
13
120
1
Order By: Relevance
“…A role in the (predictive) integration of feedback inputs could explain the increased perception threshold we observed in these patients. This is supported by observations of impaired proprioception in severely ataxic cerebellar patients (Bhanpuri et al 2013;Maschke et al 2003). It is also supported by data from pointing and reaching experiments in less affected patients (Izawa et al 2012;Synofzik et al 2008).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…A role in the (predictive) integration of feedback inputs could explain the increased perception threshold we observed in these patients. This is supported by observations of impaired proprioception in severely ataxic cerebellar patients (Bhanpuri et al 2013;Maschke et al 2003). It is also supported by data from pointing and reaching experiments in less affected patients (Izawa et al 2012;Synofzik et al 2008).…”
Section: Discussionsupporting
confidence: 68%
“…In contrast to the cerebellar patient studies mentioned above (Bhanpuri et al 2013;Maschke et al 2003), we included patients with focal cerebellar lesions who were only mildly ataxic. This had a purpose because, in general, more localized lesions will result in more specific deficits but also less prominent ones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unconscious component, controlled partially by the cerebellum, is seen soon after the infant gains neck movement control. It can be assessed by tilting body on one side and observing the eyes leveled to a horizontal line by tilting the head to opposite side (Bhanpuri, Okamura, & Bastian, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Altogether, these examples are evidence that the motor commands sent to the muscles are known by the CNS before movement onset. The internal models responsible for such predictions have been proposed to be located in the cerebellum (Bastian, 2006;Bhanpuri, Okamura, & Bastian, 2013;Cerminara, Apps, & Marple-Horvat, 2009;Diedrichsen, Verstynen, Lehman, & Ivry, 2005;Wolpert, Miall, & Kawato, 1998) and in the parietal cortex (Desmurget & Sirigu, 2009;Sirigu, Daprati, Pradat-Diehl, Franck, & Jeannerod, 1999;Wolpert, Goodbody, & Husain, 1998) (For reviews tackling these two views, see Desmurget & Grafton, 2000 as well as Blakemore & Sirigu, 2003). Regarding cerebellar internal models, neuroimaging studies have shown the strong involvement of the cerebellum during both eye-hand tracking motions (Miall & Reckess, 2002) and grip force-load force coupling (Tamada, Miyauchi, Imamizu, Yoshioka, & Kawato, 1999).…”
Section: Introductionmentioning
confidence: 99%